Aplikasi Service Kendaraan Berbasis Website Menggunakan Framework ReactJS (Studi Kasus Bengkel Sihotang Motor dan Mobil) - Anre Franciscus; Dede Sahrul (CV. Multi Kreasi Media, 2024)
The development of information technology is currently growing rapidly and can be applied in many fields of work, so many companies are trying to take advantage of technology to improve its quality, especially in the field of services where companies must be able to learn and utilize internet technology for vehicle emergency services by utilizing website-based mobile phones, Vehicle emergency service services make it easy for consumers to order services, both emergency and to book mechanical call services on certain days, especially during this covid pandemic, they are required to keep their distance. Based on these problems, the idea emerged to create a website-based application with the principle of mobile first, in which it is possible to order emergency services and book mechanical services for certain days. With this emergency service application, it is able to provide a good level of service to customers. The methodology used is Scrum, the programming language and framework used are javascript and react js. Database using PostgreSql, Tools and editor using Visual Studio. Based on the data analysis carried out, it was concluded that by applying the application in this study it could make it easier for consumers to make Emergency Service Orders which could shorten the time from long queues and make it easier for consumers when ordering emergency services to the Sihotang Car and Motorcycle Workshop.